Treatment of Neuroendocrine Tumor Liver Metastases - Mark A. Lewis; Timothy J. Hobday (International Journal of Hepatology)
In the care of patients with hepatic neuroendocrine metastases, medical oncologists should work in multidisciplinary fashion with surgeons, interventional radiologists, and radiation oncologists to assess the potential utility of liver-directed and systemic therapies. This paper addresses the various roles and evidence basis for cytoreductive surgery, thermal ablation (radiofrequency, microwave, and cryoablation), and embolization (bland embolization (HAE), chemoembolization (HACE), and radioembolization) as liver-directed therapies. Somatostatin analogues, cytotoxic chemotherapy, and the newer agents everolimus and suntinib are discussed as a means for controlling intra- and extrahepatic disease, along with peptide receptor radiotherapy (PRRT). Finally, the experience with orthotopic liver transplant for neuroendocrine tumors is described.